HUKUM ISLAM DALAM PRESPEKTIF ORIENTALIS: MENELUSURI JEJAK PEMIKRAN JOSEPH SHACHT - Muslim, Nur Aziz (Ahkam: Jurnal Hukum Islam, 2017)
Orientalism refers to studies conducted by western scholars on Islamic literatures which are considered closer to eastern habitants in term of the language used, literatures, civilization, culture, histories, set of beliefs, and the regulation. Anyway, the studies conducted by the orientalists, as a matter of fact, do not merely set targets as suspected by the majority of Moslems. To sort, the targets set by the orientalists in conducting their studies are classified into five: religion, colonialism, politic, science and technology, and economy. Joseph Shacht belongs to prominent figure of orientalist whose interest is in Hadits study. His study gives big impact on Islamic law. He mentionsb that Islamic law is not the product of theology and yurisdiction, but the product of history and sociology. His conclusion gives effect on the source of Islamic law. He views that Islamic law does not come from the God but totally the evolutional product of history and sociology. The validity of his conclusion is being questioned and criticized by Fazlurrahman. Although Joseph Shacht neglects the existence of Hadits in the hierarchy of Islamic law, his big contribution is that he has introduced the Islamic law to the secular western people.Keywords: Orientalism, Joseph Shacht, Five Targets, Historical, Sociological